An outbreak of Portuguese man-of-war (Physalia physalis - Linnaeus, 1758) envenoming in Southeastern Brazil - Haddad Júnior, Vidal [UNESP] (2013)
Introduction Portuguese man-of-war, Physalia physalis (Linnaeus, 1758), are cnidarians capable of discharging intracellular organelles filled with venom, resulting in severe envenomation in humans. Methods We report the clinical and therapeutic aspects of 331 accidents involving Portuguese man-of-war in an outbreak on the coast of the State of São Paulo, Brazil. Results The clinical manifestations of envenomation were rare and mild and mostly local, systemic reactions; there was a low rate of late complications. Conclusions The consequences of envenomation were of moderate severity, and first aid measures were effective in controlling the pain. Outbreaks of accidents involving Portuguese man-of-war occur periodically in the area without a clear explanation.